KETERAMPILAN MUSIKALISASI PUISI DENGAN TEKNIK PEMODELAN PADA SISWA KELAS KELAS IX SMP NEGERI 3 RUMBIA KABUPATEN JENEPONTO - Rusniati Rusniati (Al-Din: Jurnal Dakwah dan Sosial Keagamaan, 2020)
Abstract This research aims to improve student learning outcomes in music poetry through modeling techniques in Class IX students of SMP Negeri 3 Rumbia, Jeneponto Regency. This study, is a research that aims to make improvements that have an impact on improving student learning outcomes. The subjects in this study were class IX students of SMP Negeri 3 Rumbia, Jeneponto with a total of 41 students, while the object of the research was the entire learning process by applying modeling techniques in learning musical poetry. This research was conducted in two cycles namely cycle I and cycle II, indicators of the success of this classroom action research on aspects of the process and learning outcomes. Data collection techniques were observations (field observations, field notes), questionnaires, documentation, performance tests (performance) and recordings. The results of the research cycle 1, with the number of students who score 80 and above as many as 11 students or 26.82%. After seeing the results achieved with the provisions of the indicator of the success of 80% of students who scored ≥ 80, not yet reached the maximum results. Based on the results of observations and evaluations that have been carried out in the second cycle there was an increase in student learning outcomes in musical poetry using modeling techniques with the value of ≥ 80 totaling 39 students or 95.12% and whereas in the second cycle it only reached 26.82% with the number 11 students. Thus, it can be concluded that the learning outcomes of Class IX students of SMP Negeri 3 Rumbia, Jeneponto Regency in musical poetry will increase when using modeling techniques correctly. Keywords: Musicalisation of poetry, and modeling techniques